Battery reference book - Crompton, T. R. (Newnes, 2000)
Crompton's Battery Reference Book has become the standard reference source for a wide range of professionals and students involved in designing, manufacturing, and specifying products and systems that use batteries. This book is unique in providing extensive data on specific battery types, manufacturers and suppliers, as well as covering the theory - an aspect of the book which makes an updated edition important for every professional's library. The coverage of different types of battery is fully comprehensive, ranging from minute button cells to large installations weighing several hundred tonnes. Must-have information and data on all classes of battery in an accessible form. Essential reference for design engineers in automotive and aerospace applications, telecommunications equipment, household appliances, etc. Informs you of developments over the past five years.